A Study on Immunopathologic Effect of Thiram Toxicosis in Broiler Chicken - Subapriya, S.; Vairamuthu, S.; Manohar, B. Murali; Balachandran, C. (International Journal of Poultry Science, 2007)
An investigation was undertaken to study the body weight gain and feed conversion efficiency in broiler chicken fed with thiram a fungicide used for treating corn and storing food grains. Forty eight birds were randomly distributed into four groups of twelve each and thiram was incorporated at 15, 30 and 60 ppm into the toxin free diet for four weeks from the day of hatch. Blood samples were collected, sera separated and HI titres were measured in the control and treated sera. Birds were sacrificed at the end of second and fourth week for detailed examination of lymphoid organs. There was a significant reduction in the antibody titre in the thiram fed birds. Lymphocyte proliferation assay conducted from the lymphocytes prepared from the spleen showed significant reduction in the stimulation index. Histopathology of the lymphoid organs including bursa, spleen thymus and caecal tonsils showed lymphoid depletion to lymphocytolysis.